Chemerin, a Novel Peroxisome Proliferator-activated Receptor γ (PPARγ) Target Gene That Promotes Mesenchymal Stem Cell Adipogenesis - Muruganandan, Shanmugam (American Society for Biochemistry and Molecular Biology, 2011)
Chemerin is an adipocyte-secreted protein that regulates adipogenesis and the metabolic function of mature adipocytes via activation of chemokine-like receptor 1 (CMKLR1). Herein we report the interaction of peroxisome proliferator-activated receptor γ (PPARγ) and chemerin in the context of adipogenesis. Knockdown of chemerin or CMKLR1 expression or antibody neutralization of secreted chemerin protein arrested adipogenic clonal expansion of bone marrow mesenchymal stem cells (BMSCs) by inducing a loss of G(2)/M cyclins (cyclin A2/B2) but not the G(1)/S cyclin D2. Forced expression of PPARγ in BMSCs did not completely rescue this loss of clonal expansion and adipogenesis following chemerin or CMKLR1 knockdown. However, forced expression and/or activation of PPARγ in BMSCs as well as non-adipogenic cell types such as NIH-3T3 embryonic fibroblasts and MCA38 colon carcinoma cells significantly induced chemerin expression and secretion. Sequence analysis revealed a putative PPARγ response element (PPRE) sequence within the chemerin promoter. This PPRE was able to confer PPARγ responsiveness on a heterologous promoter, and mutation of this sequence abolished activation of the chemerin promoter by PPARγ. Chromatin immunoprecipitation confirmed the direct association of PPARγ with this PPRE. Treatment of mice with rosiglitazone elevated chemerin mRNA levels in adipose tissue and bone marrow coincident with an increase in circulating chemerin levels. Together, these findings support a fundamental role for chemerin/CMKLR1 signaling in clonal expansion during adipocyte differentiation as well as a role for PPARγ in regulating chemerin expression.